2018
DOI: 10.1016/j.jdiacomp.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes, depressive symptoms and disability over a 15-year follow-up period in older Mexican Americans living in the southwestern United States

Abstract: AIMS To evaluate how depression and diabetes severity impacts disability progression among Mexican Americans over a 15-year period. METHODS We used seven waves of the Hispanic Established Population for the Epidemiologic Study of the Elderly (H-EPESE). Primary disability outcomes included the Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) scales. Explanatory variables included time since diagnosis with diabetes (no type 2 diabetes, 1-10, 11-20, 21+), an indicator of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
1
17
0
3
Order By: Relevance
“…Some diabetes studies have examined Hispanics as a homogeneous group, 11,12 while other studies like the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) have focused on specific Hispanic subgroups of the US population. For those diabetes studies of Hispanic subgroups, the focus has been solely on Mexican Americans 13,14 residing in the United States. [13][14][15] Studies (ie, the HCHS/SOL and San Antonio Heart) on Hispanic subgroups have found Mexicans to have the highest diabetes prevalence rate [16][17][18] and to have a significant secular trend in the 7-to 8-year incidence of diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some diabetes studies have examined Hispanics as a homogeneous group, 11,12 while other studies like the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) have focused on specific Hispanic subgroups of the US population. For those diabetes studies of Hispanic subgroups, the focus has been solely on Mexican Americans 13,14 residing in the United States. [13][14][15] Studies (ie, the HCHS/SOL and San Antonio Heart) on Hispanic subgroups have found Mexicans to have the highest diabetes prevalence rate [16][17][18] and to have a significant secular trend in the 7-to 8-year incidence of diabetes.…”
mentioning
confidence: 99%
“…For those diabetes studies of Hispanic subgroups, the focus has been solely on Mexican Americans 13,14 residing in the United States. [13][14][15] Studies (ie, the HCHS/SOL and San Antonio Heart) on Hispanic subgroups have found Mexicans to have the highest diabetes prevalence rate [16][17][18] and to have a significant secular trend in the 7-to 8-year incidence of diabetes. 15 These findings show the growing diabetes rates among Mexicans in the United States.…”
mentioning
confidence: 99%
“…The number of Mexican American older adults aged 65 years and older is growing rapidly because of the high immigration volume from Mexico, persistent high fertility rates, low mortality rates, and the natural aging process (Angel & Angel, 1998; Federal Interagency Forum on Aging-Related Statistics, 2012; Pew Hispanic Center, 2016). Many older Mexican immigrants face mental health challenges, of which, depressive symptoms are the most common one (Black & Markides, 1999; Salinas, Gonzalez, & Al Snih, 2018). The Hispanic Established Population for the Epidemiologic Study of the Elderly reported that the prevalence of depression (16 or more Center for Epidemiologic Studies-Depression score) was 21.2% among older Mexican Americans (Salinas et al., 2018).…”
mentioning
confidence: 99%
“…Many older Mexican immigrants face mental health challenges, of which, depressive symptoms are the most common one (Black & Markides, 1999; Salinas, Gonzalez, & Al Snih, 2018). The Hispanic Established Population for the Epidemiologic Study of the Elderly reported that the prevalence of depression (16 or more Center for Epidemiologic Studies-Depression score) was 21.2% among older Mexican Americans (Salinas et al., 2018). Elevated levels of depressive symptoms concomitant with chronic conditions such as diabetes, heart disease, hypertension, cancer, and stroke increase the risk of mortality and disability among Mexican American older adults (Black & Markides, 1999; Salinas et al., 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation